Social spending in South Asia - an overview of government expenditure on health, education and social assistance - Carolina Bloch (International Policy Centre for Inclusive Growth (IPC-IG), 2020)
Many South Asian countries experienced changes in government and strong economic growth since the early 2000s. Poverty and social exclusion have received growing attention, and many governments in the region strengthened their commitments to ensure equal access to basic healthcare, education and adequate income. However, progress has been uneven and efforts to address structural challenges related to poverty and inequality are hindered by gaps in budgetary and institutional capacity.
Keywords: 330; Public spending; social assistance; South Asia; poverty reduction; fiscal consolidation